(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2025)
Background. The Russian-Ukrainian war has become a platform for changes in gender issues: women are actively participating in the country’s defense, performing duties that were traditionally male. Currently, women serve not only in medical units or administrative positions but also perform combat missions as sappers, artillery operators, snipers, reconnaissance operatives, and more. Thus, the transformation of female service members’ value orientations is a multi-factorial process dependent on various social and psychological factors. In combat conditions, general values undergo significant changes under the influence of extreme situations, the need to make rapid and accurate decisions, and constant exposure to stress. At the same time, women demonstrate high moral resilience, capacity for self-realization, and effective adaptation to critical conditions, becoming an important component of the country’s defense capabilities. Methods. The implementation of the research goal was carried out through theoretical and methodological analysis of servicemembers’ value orientations, identification of psychological features and mechanisms of transformation of female service members’ value orientations during wartime, and empirical research of value orientations among female service members with different levels of combat experience. Results. The conducted research confirmed that female service members not only adapt to the challenges of war but also form new moral and ethical standards. Their dominant values—patriotism, collectivism, and professionalism—serve as the foundation for effective service and the maintenance of high moral resilience. Extreme conditions foster the transformation of value orientations, making women in the Armed Forces of Ukraine a critical element in the country’s overall defense capability. Conclusions. The obtained results can serve as a platform for developing new research projects, improving the social adaptation of female service members, and integrating Ukraine into international gender initiatives in the military sphere.